Emergency medical services clinicians in the United States are increasingly exposed to death - Amelia Breyre; Remle P. Crowe; Antonio R. Fernandez; Alexandra Jabr; J. Brent Myers; Douglas F. Kupas (Journal of the American College of Emergency Physicians Open)
Abstract Introduction Exposure to patient death places healthcare workers at increased risk for burnout and traumatic stress, yet limited data exist exploring exposure to death among emergency medical services (EMS) clinicians. Our objective was to describe changes in EMS encounters involving on‐scene death from 2018 to 2021. Methods We retrospectively analyzed deidentified EMS records for 9‐1‐1 responses from the ESO Data Collaborative from 2018 to 2021. We identified cases where patient dispositions of death on scene, with or without attempted resuscitation, and without EMS transport. A non‐parametric test of trend was used to assess for monotonic increase in agency‐level encounters involving on‐scene death and the proportion of EMS clinicians exposed to ≥1 on‐scene death. Results We analyzed records from 1109 EMS agencies. These agencies responded to 4,286,976 calls in 2018, 5,097,920 calls in 2019, 4,939,651 calls in 2020, and 5,347,340 calls in 2021.The total number of encounters with death on scene rose from 49,802 in 2018 to 60,542 in 2019 to 76,535 in 2020 and 80,388 in 2021. Agency‐level annual counts of encounters involving death on scene rose from a median of 14 (interquartile range [IQR], 4–40) in 2018 to 2023 (IQR, 6–63) in 2021 (P‐trend < 0.001). In 2018, 56% of EMS clinicians responded to a call with death on scene, and this number rose to 63% of EMS clinicians in 2021 (P‐trend < 0.001). Conclusion From 2018 to 2021, EMS clinicians were increasingly exposed to death. This trend may be driven by COVID‐19 and its effects on the healthcare system and reinforces the need for evidence‐based death notification training to support EMS clinicians.